Maxillo-orbital gunshot trauma in a pediatric patient - Maram Adil Mansour; Elnagar E. Elgasim; Esameldin Adam Nagi; Ibtisam Hussein; Malaz Mansour (Elsevier, 2024)
Gunshot injuries to the maxillofacial region vary in severity from minor harm to critical situations necessitating urgent medical intervention. Effective handling of facial gunshot wounds mandates a multidisciplinary approach to deliver thorough care to the individual.We present a pediatric patient presenting to the Emergency Department following an accidental machine gun injury.